2016
DOI: 10.1016/j.lfs.2016.02.043
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of endothelin-1 and NLRP3 inflammasome activation in HT22 hippocampal cells in diabetes

Abstract: Diabetes increases the risk and worsens the progression of cognitive decline. Diabetic rats treated with the dual endothelin receptor antagonist bosentan, have been shown to improve hippocampal-based cognitive deficits. The NLRP3 inflammasome has been implicated in vascular complications of diabetes. We hypothesized that diabetes-mediated increase in endothelin-1 (ET-1) in hippocampal cells causes NLRP3 activation and inflammation. An in vitro model was employed by exposing HT22 hippocampal cells to normal (25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 31 publications
6
25
0
Order By: Relevance
“…In the hypothalamus, cell type was less discernable. While resident immune cells, such as microglia, are principally thought to produce and elaborate inflammatory cytokines, several studies show that human neurons contain an inflammasome [61, 62]. In cultured primary cortical neurons, ethanol can induce caspase-1 activation and HMGB1 release [63].…”
Section: Discussionmentioning
confidence: 99%
“…In the hypothalamus, cell type was less discernable. While resident immune cells, such as microglia, are principally thought to produce and elaborate inflammatory cytokines, several studies show that human neurons contain an inflammasome [61, 62]. In cultured primary cortical neurons, ethanol can induce caspase-1 activation and HMGB1 release [63].…”
Section: Discussionmentioning
confidence: 99%
“…Endothelin (ET), a neuromodulator peptide that exists in three isoforms ET-1, -2, and -3 (Inoue et al, 1989), activates two ET receptor subtypes, ET-A and ET-B, with varying degrees of selectivity (Arai et al, 1990). Although high glucose increases ET level in vivo (Schneider et al, 2002) or decreases its level in in vitro models (Ward and Ergul, 2016), the role of ET in high glucose-evoked neurotoxicity remains elusive due to controversial reports on ET effects on the nervous system. For example, ET activation of the ET-A receptor is implicated in cerebral ischemia/reperfusion injury (Matsuo et al, 2001) and in other reports ET confers neuroprotection through both ET-A and -B receptors (Laziz et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, some studies showed that ET A or dual ET A /ET B receptor antagonism is neuroprotective and improves outcomes after ischemia reperfusion injury of the brain (Dawson et al 1999, Gupta et al 2005, Matsuo et al 2001, Zhang et al 2008. Moreover, endothelial cell specific overexpression of ET-1 worsened cerebral damage (Leung et al 2009) and ET-1 induced degeneration of cultured motor neurons (Ward et al 2016). On the other hand, some studies suggested that the ET receptor blockade exacerbates brain infarction (Chuquet et al 2002) and ET-1 improves neuronal survival in cell culture models (Leung et al 2009, Ward et al 2016.…”
Section: Integrationmentioning
confidence: 99%
“…Moreover, endothelial cell specific overexpression of ET-1 worsened cerebral damage (Leung et al 2009) and ET-1 induced degeneration of cultured motor neurons (Ward et al 2016). On the other hand, some studies suggested that the ET receptor blockade exacerbates brain infarction (Chuquet et al 2002) and ET-1 improves neuronal survival in cell culture models (Leung et al 2009, Ward et al 2016.…”
Section: Integrationmentioning
confidence: 99%
See 1 more Smart Citation